IMPACTS OF FREE EDUCATION IMPLEMENTATION ON CLASSROOM TEACHING STRATEGIES; A STUDY OF MOROGORO MUNICIPALITY - Yusufu A. Pongwa; Omer Solomon, W (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The purpose of the study was to explore impacts of free education implementation on classroom teaching strategies in Morogoro municipal council. The study was guided by three objectives which are to identify the teaching strategies which affected by the implementation of free secondary education in Morogoro municipality. To determine the challenges faced by teachers when using the identified teaching strategies during the time of implementing free secondary education in Morogoro municipality and To suggest the remedial measures to the challenges faced by teachers when employing classroom teaching strategies during the time of implementing free education in Morogoro municipality. The study employed mixed approach by integrating both quantitative and qualitative research approaches. Method of data collection such as questionnaire and interview was used to collect data. The study findings revealed that, all teaching strategies affected by the implementation of free secondary education exclude one class, two instructors teaching strategies. These results indicate that, the introduction of free secondary education resulted into deteriorated school infrastructure since some of the key stakeholders of education such as parents/communities thought it is the responsibility of the Government. This tends to affect classroom teaching strategies since school infrastructures like laboratory, library, toilet facilities, canteen, classrooms, and computers can help students to enhance their motivation on learning. Due to this, deteriorated school infrastructure might a barrier that lead to the realization of education as a fundamental constitutional right. Shortage of classrooms affects classroom teaching strategies since teaching in an overcrowded classroom can cause many problems such as stress and frustration for teachers. In case of student’s shortage of classrooms, these results into problems like truancy, noise making, medical/health problems, fighting among others. The study recommended there is need for informed infrastructure if the large classes have to be managed and taught effectively by the classroom teaching strategies. The ministry of education to consider those teaching resources so as to enable teachers to be effectively employs teaching strategies. Policy makers are called upon to mage teachers in training and or in-service training that would make effectives. The educational managers are required to increase the number of teaching staffs so as to release the current teachers from heavy workload and overclouded class so that the teaching strategies to classroom.